Short Term Outcome of Dorsal Onlay Buccal Mucosa Graft for the Management of Bulbar Urethral Stricture (Bangladesh Journal of Urology, 2020)
Objective: To assess the success of buccal mucosal graft (BMG) urethroplasty by the dorsal onlay technique in long anterior urethral stricture (> 2 cm long).Method: This prospective interventional study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology, Sher-e-Bangla Nagar, Dhaka from January 2016 to December 2017 over a period of two years. Thirty three patients with primary and recurrent stricture of anterior urethra involving the bulbar urethra scheduled for single buccal mucosa graft urethroplasty were included in this study. Written consent was taken from each patient. Patients with stricture at posterior urethra or at distal penile urethra or stricture length